CT Scan Imaging in Tuberculosis and Lung Cancer: A Case Report in Lung Hospital - Lestari, Lilik; Sultansyah, Muhammad Harris Sis (RSUP Dr. Kariadi, 2023)
Background: Tuberculosis is a contagious infectious disease that attacks various organs, especially the lungs. Chest CT scan modalities have a role in helping the diagnosis of tuberculosis and lung cancer. This case report presents a rare case of two women diagnosed with tuberculosis and lung cancer. Cases Presentation: Two women aged 43 and 42 years came to the radiology department with a history of chest pain, loss of appetite, and cough, and underwent tuberculosis therapy by taking medication for two months. The patient underwent chest x photo thorax, abdominal ultrasound, thoracic CT scan, and a biopsy was performed with CT scan guiding. Discussion: The findings of this case are consistent with previous studies which explained that radiological CT scans found tuberculosis with lung cancer. In the lung window, CT scan chest contrast found cystic bronchiectasis. Other results showed an encapsulated pleural effusion in the right hemithorax, compression atelectasis, and multiple lymphadenopathies. Conclusion: CT scan imaging simultaneously can show the occurrence of tuberculosis and lung cancer. Lung cancer that worsens can cause adenocarcinoma with metastasis spreading to other organs.